Forest Vegetation Survey and Classification with Special Reference to South India I. Vegetation Survey and Quadrat Analysis - Sharma, S. K.; George, M.; Pasad, K. G. (Indian Forester, 1983)
The paper deals with the standardisation of quadrat size and recording of vegetation data with special reference to south Indian forests for its classification into communuties and mapping. The data were collected from south Indian dry deciduous, moist deciduous, semi-evergreen and evergreen type of forests. The minimal area for tree quadrat depends on the forest type and varies from 400 m3 for dry and moist deciduous forests to 900 m2. For semi-evergreen and evergreen forests. Quadrat size of 9 m2 was minimal for shurbs irrespective of forests types. Methods of laying out quadrat for convenient and speedy recording of vegetation data have been described.